Robotic-Assisted Sentinel Lymph Node Mapping With Indocyanine Green in Pelvic Malignancies: A Systematic Review and Meta-Analysis - Wu, Yuqing; Jing, Jibo; Wang, Jinfeng; Xu, Bin; Du, Mulong; Chen, Ming (Frontiers in Oncology, 2019)
Objective: Newer technologies such as near-infrared (NIR) imaging of the fluorescent dye indocyanine green (ICG) and daVinci Xi Surgical System have become promising tools for sentinel lymph node (SLN) mapping. This meta-analysis was conducted to comprehensively evaluate the diagnostic value of SLN in assessing lymph nodal metastasis in pelvic malignancies, using ICG with NIR imaging in robotic-assisted surgery. Materials and methods: A literature search was conducted using PubMed for studies in English before April 2019. The detection rate, sensitivity of SLN detection of metastatic disease, and factors associated with successful mapping (sample size, study design, mean age, mean body mass index, type of cancer) were synthesized for meta-analysis. Results: A total of 17 articles including 1059 patients were finally included. The reported detection rates of SLN ranged from 76% to 100%, with a pooled average rate of 95% (95% CI: 93-97; 17 studies). The sensitivity of SLN detection of metastatic disease ranged from 50% to 100% and the pooled sensitivity was 86% (95% CI: 75-94; 8 studies). There were no complications related to ICG administration reported. Conclusions: NIR imaging system using ICG in robotic-assisted surgery is a feasible and safe method for SLN mapping. Due to its promising performance, it is considered to be an alternative to a complete pelvic lymph node dissection.